Histórias e culturas indígenas outras em "Índio Presente" (2017): o potencial da produção midiática na desconstrução de equívocos - Moreira, Tássita de Assis (2021)
The reproduction of stereotyped ideas about indigenous peoples persists even after centuries of struggle and resistance. In Brazilian society, and especially in the school environment, common sense prevails with an immense destructive potential and the invitation to rethink educational practices may prove to be an interesting path to take. The objective of this research is to reflect on the presence of indigenous and non-indigenous people in the audiovisual production of the documentary series Indio Presente (2017) and its potential in deconstructing mistakes and valuing indigenous histories and cultures. For this discussion, Cultural Studies by Hall (2003), Larrosa and Skliar (2001), Decolonial Studies with Quijano (2005), Mignolo (2017) and - specifically in indigenous history - Smith (2018) were listed as theoretical and methodological devices, and on Critical Interculturality with Walsh (2008), Candau e Russo (2010), as well as the analysis from the “engaged look” proposed by Mauad (2008), the intercultural communication in Gallois (2004) and the materiality of the audiovisual product in Souza (2004) and Guilherme (2018). The analysis of the thirteen episodes that make up the documentary series was carried out through three categories: The deconstruction of the founding myth; Contributions to a decolonial pedagogy; Interculturality in the production of the series, and conducting interviews with indigenous and non-indigenous directors and producers. As theoretical research references in education, decolonial pedagogy and teaching of indigenous themes, this research is based on the studies of Silva Jr. and Souza (2016), Silva and Costa (2018), Munduruku (2017) and Kayapó (2020). The results of the analyzes indicate that, from the contribution of indigenous people producing together with non-indigenous, the audiovisual product of the documentary series can contribute to the deconstruction of stereotypes and mistakes historically reproduced inside and outside the school space, as well as contributing to the appreciation and dissemination of histories, cultures, people and indigenous peoples.